Ambition and Talent - Botond Koszegi; Wei Li (Hungarian Academy of Sciences, Institute of Economics, 2002)
We develop a career concerns model in which agents differ in taste for income in addition to ability, and derive basic implications of this framework. We argue that the model captures important aspects of ambition. Since ambitious agents are expected to work harder and therefore be paid more than unambitious ones, everyone might be induced to work hard to prove that they are ambitious. On the other hand, proving ones ambition can be detrimental, because past outputs will be taken by the principal to reflect lower ability. Thus, ambition-proving incentives are likely to increase effort early in the career and decrease it later. Over a long horizon, ambition-proving incentives have a tendency to bootstrap themselves, and, if this effect is strong enough, to create significant incentives with little else motivating the agent. Finally, we discuss in detail two consequences of our framework for organizational design. To maximize effort, the principal wants to cater incentives to the best-performing employees, and wants to observe a measure of the agents effort (say, his hours) early, but not late, in the career.
Keywords: 330